2013
DOI: 10.3389/fncel.2013.00015
|View full text |Cite
|
Sign up to set email alerts
|

Novel molecular changes induced by Nrg1 hypomorphism and Nrg1-cannabinoid interaction in adolescence: a hippocampal proteomic study in mice

Abstract: Neuregulin 1 (NRG1) is linked to an increased risk of developing schizophrenia and cannabis dependence. Mice that are hypomorphic for Nrg1 (Nrg1 HET mice) display schizophrenia-relevant behavioral phenotypes and aberrant expression of serotonin and glutamate receptors. Nrg1 HET mice also display idiosyncratic responses to the main psychoactive constituent of cannabis, Δ9-tetrahydrocannabinol (THC). To gain traction on the molecular pathways disrupted by Nrg1 hypomorphism and Nrg1-cannabinoid interactions we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 100 publications
2
20
0
Order By: Relevance
“…In fact, chronic administration of THC impairs spatial memory and reduces a learning-related transcription factor (zif268) expression in the mouse forebrain [83]. This is consistent with the significant reduction in the number of synapses per unit volume (44%) as well as a reduction in the dendritic length of CA3 pyramidal neurons, as observed in rats receiving high doses of THC (10 to 60 mg/ kg), during a long period of treatment (90 days) [84].…”
Section: The Opposite Effectsupporting
confidence: 66%
“…In fact, chronic administration of THC impairs spatial memory and reduces a learning-related transcription factor (zif268) expression in the mouse forebrain [83]. This is consistent with the significant reduction in the number of synapses per unit volume (44%) as well as a reduction in the dendritic length of CA3 pyramidal neurons, as observed in rats receiving high doses of THC (10 to 60 mg/ kg), during a long period of treatment (90 days) [84].…”
Section: The Opposite Effectsupporting
confidence: 66%
“…Thus, ErbB4 and CB1 might interact in the substantia nigra and thereby regulate the hyper-locomotor phenotype of Nrg1 mutant mice. Nrg1 also conferred opposing effects of THC on 5-HT2A receptor expression in the insular cortex and NMDA receptor binding was selectively increased in the hippocampus and cingulate cortex of Nrg1 HET mice (Long et al, 2013) (for a better mechanistic understanding of Nrg1 -THC interaction on NMDA receptor expression in the hippocampus see Spencer et al, 2013). …”
mentioning
confidence: 99%
“…This is consistent with the idea that neuroinflammatory processes are implicated in the pathophysiology of schizophrenia and other psychiatric conditions. Additionally, NAPE‐PLD is upregulated in adolescent Nrg1 HET mice treated with ∆9‐THC, compared to a vehicle‐treated group, suggesting a possible mechanism of ∆9‐THC in regulation of anandamide levels. Initially, it was believed that phytocannabinoids like ∆9‐THC only has CB1/CB2 agonist properties, but current studies have shown the effects of these compounds in enzymatic process, and with the analyses we reported a role of ∆9‐THC in NAPE‐PLD (Figure ).…”
Section: Schizophrenia and Endocannabinoid Systemmentioning
confidence: 96%
“…Although some studies applying genetic, image, and behavioral task methodologies, as described above (see Schizophrenia and Endocannabinoid System Section), have pinpointed a role of this system in the pathophysiology of schizophrenia, few proteomic investigations have been carried out with the same goals in mind. In the case of preclinical studies, hippocampal samples from the neuregulin 1 transmembrane heterozygous (Nrg1 HET) mouse—a model of schizophrenia—was used in a proteome profiling analysis . These animals and their wild‐type (WT) littermates were treated with ∆9‐THC, and the proteome analyses demonstrated that Nrg1 HET mice presented changes in the abundance of proteins involved in several biological processes (Table ).…”
Section: Schizophrenia and Endocannabinoid Systemmentioning
confidence: 99%